Nitrogen‐fixing bacterial communities in invasive legume nodules and associated soils are similar across introduced and native range populations in Australia. (11th March 2016) - Birnbaum, Christina; Bissett, Andrew; Thrall, Peter H.; Leishman, Michelle R.
Abstract: Aim: Understanding the interactions between invasive legumes and soil biota in both native and introduced ranges could assist in managing biological invasions. We analysed the diversity of putative nitrogen‐fixing bacteria (NFB, i.e. nifH gene present) associated with five invasive legumes, four Acacia spp. and a sister taxon Paraserianthes lophantha in introduced and native range populations in Australia. We predicted that, because these host species are widely distributed, they are likely to encounter different nitrogen‐fixing bacterial communities in soils and nodules across their introduced and native ranges. Location: Australia. Methods: NifH genes were amplified from rhizosphere soils collected from beneath each species (multiple populations) within their native and introduced range and directly from nodules collected from plants previously grown in the glasshouse using field‐collected soil as inoculum. NifH gene sequences from soils and nodules were 454 pyrosequenced and assigned to taxonomic groups based on nifH consensus taxonomy. Results: We found no difference in the NFB community of soils or nodules between native and introduced ranges across the five species, suggesting that these legumes encounter similar NFB communities in soils across Australia. Bradyrhizobium was the most abundant rhizobial genus present in both soils and nodules . Bradyrhizobium species found in nodules were significantly different across the ranges for A. longifolia . Main conclusions: The results indicate that these invasive legumes have similar nitrogen‐fixing bacterial communities in their rhizosphere and nodules across Australia, with the exception of A. longifolia . This species has diverse Bradyrhizobium genotypes in its nodules suggesting that A. longifolia may be a more generalist host compared to the other four legumes. Thus, it is unlikely that the invasive success of these legumes is constrained by the absence of suitable bacterial symbionts in soil. Better knowledge of legume–soil interactions could facilitate more informed and effective management of invasive legumes in their introduced ranges in Australia and elsewhere.